2007
DOI: 10.1016/s0377-1237(07)80098-0
|View full text |Cite
|
Sign up to set email alerts
|

Tracheo-esophageal Puncture (TEP) for Voice Rehabilitation in Laryngectomised Patients Blom-singer® Vs Provox® Prosthesis : Our Experience

Abstract: In Indian scenario where illitracy amongst the patients hinders in maintainence of Blom-Singer® prosthesis, Provox® indwelling value is an appropriate choice for voice rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In a review by Sara Cruz et al in Portugal, mean device life were 1-74 months for primary prosthesis and 1-24 months for secondary prosthesis [33]. Two Indian studies reported mean prosthesis longevity of 18 and 15 months, respectively [25,44]. The mean life of our prosthesis was 16 months (1-42 months), which is similar to the experience of the other published Indian series (Table 4).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a review by Sara Cruz et al in Portugal, mean device life were 1-74 months for primary prosthesis and 1-24 months for secondary prosthesis [33]. Two Indian studies reported mean prosthesis longevity of 18 and 15 months, respectively [25,44]. The mean life of our prosthesis was 16 months (1-42 months), which is similar to the experience of the other published Indian series (Table 4).…”
Section: Discussionsupporting
confidence: 81%
“…The prosthesis device life can also vary across regions due to number of reasons, including diet, patient preference, reimbursement and voice expectations, and tolerance of periods of minor leakage prior to replacement. The life of the voice prosthesis has been reported to be anywhere between 2 and 14 months based on the different group of patients, devices, and regions studied [10,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of verbal communication after total laryngectomy reduces the quality of life and leaves the patient severely handicapped. 1,2 Prompt and effective voice restoration is critical for these patients. Voice restoration using a tracheoesophageal puncture (TEP) has become the current treatment of choice for postlaryngectomy speech rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, the goal is not just creation of an intact neopharynx that does not leak. The luminal diameter of this neopharynx should be sufficient to allow for the passage of food bolus, should not be so flaccid as to adversely affect post-operative voice quality, and should allow for either primary or secondary tracheoesophageal voice restoration 10 …”
Section: Introductionmentioning
confidence: 99%